As políticas de formação inicial de professores em exercício no Brasil - Bolson, Janaína Boniatti (Universidade do Vale do Rio dos Sinos, 2016)
This thesis aims to research the initial training of teachers in primary education, and proposes to problematize how the initial training of Brazilian teachers in the basic education schools is constituted. The objective of this investment was to know the constitution of the initial training of the teacher in exercise from the analysis of the policies that generate different training practices, emerging in Brazil in the period of 1996, 1997, 2000 to 2002 and 2006 to 2010. , The concepts of Foucauldian-inspired discourse and Stephen Ball's policy cycle were used. On the basis of such a reference, the material was invested in extracting statements that make it possible to perceive the composition of a policy cycle that begins with the production of data on the school population and the quality of education in basic education, including the creation of policies and The development of actions capable of reversing educational problems and statistics on Brazilian school education, disseminated nationally and internationally. From the set of policies analyzed, the following cycle was observed: the existence of a context of influence composed of international organizations that allowed the formulation of conditions for Brazil to raise its indices of quality in education in the national and international scenario ; (LDB 9394/96), a context for the production of texts, that is, policies and / or programs were created to meet a localized demand for in-service teacher training (since these were Urgent, especially if we look at the historical trajectory of the country in this sense) that did not have adequate training for the exercise of the profession; These policies and / or programs were incorporated in the context of the practice by the Higher Education Institutes, colleges and universities as something to be put into action urgently, since Brazilian education presents a sort of historical deficit carried out by the authors of the policies throughout the time; The impact produced by these policies has brought results, perhaps not expected from the action of the first context (of influence), since the training of these practicing teachers was based much more on the lightness of a certification, than on the quality of a Training for the exercise of their profession;These policies and / or programs were incorporated in the context of the practice by the Higher Education Institutes, colleges and universities as something to be put into action urgently, since Brazilian education presents a sort of historical deficit carried out by the authors of the policies throughout the time; The impact produced by these policies has brought results, perhaps not expected from the action of the first context (of influence), since the training of these practicing teachers was based much more on the lightness of a certification, than on the quality of a Training for the exercise of their profession; Finally, in the context of political strategies, what is noticeable in the formulation of policies is the emphasis on the role of government in solving problems, which denotes a state vision restricted to political agents. At the end of the research it was possible to affirm that the initial teacher training policies are recurrent in our country, so there is little innovation in the constitution of these teacher training policies, in which they produce a specific cycle that I call the training cycle of Teachers.
Keywords: Formação de professores em exercício; Ciclo de políticas; Políticas de formação; In-service teacher training; Policy cycle; Training policies; ACCNPQ::Ciências Humanas::Educação